RNA-Binding Proteins and Alternative Splicing Genes Are Coregulated in Human Retinal Endothelial Cells Treated with High Glucose - Hongran Zhao; Hui Kong; Bozhao Wang; Sihui Wu; Tianran Chen; Yan Cui (Journal of Diabetes Research)
To explore the relevant RNA-binding proteins (RBPs) and alternative splicing events (ASEs) in diabetic retinopathy (DR). We devised a comprehensive work to integrate analyses of the differentially expressed genes, including differential RBPs, and variable splicing characteristics related to DR in human retinal endothelial cells induced by low glucose and high glucose in dataset GSE117238. A total of 2320 differentially expressed genes (DEGs) were identified, including 1228 upregulated genes and 1092 downregulated genes. Further analysis screened out 232 RBP genes, and 42 AS genes overlapped DEGs. We selected high expression and consistency six RBP genes (FUS, HNRNPA2B1, CANX, EIF1, CALR, and POLR2A) for coexpression analysis. Through analysis, we found eight RASGs (MDM2, GOLGA2P7, NFE2L1, KDM4A, FAM111A, CIRBP, IDH1, and MCM7) that could be regulated by RBP. The coexpression network was conducted to further elucidate the regulatory and interaction relationship between RBPs and AS. Apoptotic progress, protein phosphorylation, and NF-kappaB cascade revealed by the functional enrichment analysis of RASGs regulated by RBPs were closely related to diabetic retinopathy. Furthermore, the expression of differentially expressed RBPs was validated by qRT-PCR in mouse retinal microvascular endothelial cells and retinas from the streptozotocin mouse model. The results showed that Fus, Hnrnpa2b1, Canx, Calr, and Polr2a were remarkedly difference in high-glucose-treated retinal microvascular endothelial cells and Fus, Hnrnpa2b1, Canx, and Calr were remarkedly difference in retinas from streptozotocin-induced diabetic mice compared to control. The regulatory network between identified RBPs and RASGs suggests the presence of several signaling pathways possibly involved in the pathogenesis of DR. The verified RBPs should be further addressed by future studies investigating associations between RBPs and the downstream of AS, as they could serve as potential biomarkers and targets for DR.